Ethanolamine and Vinyl–Ether Moieties in Brain Phospholipids Modulate Behavior in Rats - MST Zenika Nasrin; Shuhei Kikuchi; Yasuhiro Uchimura; Mina Yoshioka; Shin-ya Morita; Tomoya Kobayashi; Yusuke Kinoshita; Yoshio Furusho; Hitoshi Tamiaki; Daijiro Yanagisawa; Jun Udagawa (NeuroSci)
Plasmalogens are brain-enriched phospholipids with a vinyl–ether bond at the sn-1 position between the glycerol backbone and the alkyl chain. Previous studies have suggested that plasmalogens modulate locomotor activity, anxiety-like behavior, and cognitive functions in rodents; however, the specific moieties contributing to behavioral regulation are unknown. In this study, we examined the behavioral modulation induced by specific phospholipid moieties. To confirm the permeability of phospholipids in injected liposomes, we measured the fluorescence intensity following intravenous injection of liposomes containing ATTO 740-labeled dioleoylphosphatidylethanolamine. Then, we compared the behavioral effects following injection of liposomes composed of egg phosphatidylcholine (PC) and 1-stearoyl-2-docosahexaenoyl-sn-glycero-3-phosphoethanolamine (PE 18:0/22:6), PC 18:0/22:6, 1-(1Z-octadecenyl)-2-docosahexaenoyl-sn-glycero-3-phosphoethanolamine (PE P-18:0/22:6), or PC P-18:0/22:6, into the tail vein of male rats. The time spent in the central region of the open field was significantly reduced after injection of PE 18:0/22:6, harboring an ester bond at sn-1 compared to controls. Furthermore, the discrimination ratio in the novel object recognition test was significantly higher in PC 18:0/22:6 compared to PE 18:0/22:6, suggesting that the substitution of ethanolamine with choline can enhance recognition memory. We demonstrate that the structures of the sn-1 bond and the hydrophilic moiety in the phospholipids can modulate exploratory behaviors and recognition memory in rodents.